The UBE2D ubiquitin conjugating enzymes: Potential regulatory hubs in development, disease and evolution - Roman-Trufero, Monica; Dillon, Niall (Frontiers in Cell and Developmental Biology, 2022)
Ubiquitination of cellular proteins plays critical roles in key signalling pathways and in the regulation of protein turnover in eukaryotic cells. E2 Ubiquitin conjugating enzymes function as essential intermediates in ubiquitination reactions by acting as ubiquitin donors for the E3 ubiquitin ligase enzymes that confer substrate specificity. The members of the UBE2D family of E2 enzymes are involved in regulating signalling cascades through ubiquitination of target proteins that include receptor tyrosine kinases (RTKs) and components of the Hedgehog, TGF and NFB pathways. UBE2D enzymes also function in transcriptional control by acting as donors for ubiquitination of histone tails by the Polycomb protein Ring1B and the DNA methylation regulator UHRF1 as well as having roles in DNA repair and regulation of the level of the tumour suppressor p53. Here we review the functional roles and mechanisms of regulation of the UBE2D proteins including recent evidence that regulation of the level of UBE2D3 is critical for controlling ubiquitination of specific targets during development. Cellular levels of UBE2D3 have been shown to be regulated by phosphorylation, which affects folding of the protein, reducing its stability. Specific variations in the otherwise highly conserved UBE2D3 protein sequence in amniotes and in a subgroup of teleost fishes, the Acanthomorpha, suggest that the enzyme has had important roles during vertebrate evolution.